Artisanal fishers on the Kenyan coast : household livelihoods and marine resource management - Hoorweg, Jan (Afrika-Studiecentrum series ;, 2009)
Overexploitation of natural resources is often associated with poverty among local populations. A multi-disciplinary team studied artisanal fishers along the Kenyan coast on the Indian Ocean. The main focus of the research was on income diversification of fishers, the pressure on marine resources and the relation between the two. Income diversification did not reduce the pressure on the marine environment. Rather, indications are that many part-time fishers are entering the profession. Moreover, fishers with alternative employment stayed in-shore and used damaging gear more often. Policies to stimulate employment opportunities for coastal communities cannot be expected to lessen the pressure on marine resources and need to be planned carefully in terms of industry location, labour requirements and degree of coastal pollution.